Transcatheter arterial embolization using N-butyl-2 cyanoacrylate Glubran® 2 for acute massive pancreati coduodenal arterial hemorrhage - Gong, Maofeng; Liu, Zhengli; Kong, Jie; Zhao, Boxiang; He, Xu; Gu, Jianping; Su, Haobo (Frontiers in Materials, 2022)
Purpose Acute massive pancreaticoduodenal artery (PDA) hemorrhage represents an urgent condition. Here, we report our experience in transcatheter arterial embolization (TAE) using N-butyl-2 cyanoacrylate (NBCA) Glubran® 2 for this condition. Methods A retrospective study of 10 consecutive patients (mean, 55.215.9 years; range, 27-74 years) was conducted from April 2015 to April 2021. The data, including baseline characteristics, control of active PDA hemorrhage (the technical and clinical outcomes), volumes of Glubran 2, and related complications, were collected from medical archives. Technical success was defined as complete occlusion of bleeding vessels on the final arteriogram. Clinical success was defined as the sustained resolution of symptoms or signs of PDA hemorrhage without the need for repeat endovascular or surgical treatment after TAE. Safety was evaluated based on the occurrence of complications. Results Glubran 2 was empirically used for 6 patients (6/10) with PDA hemorrhage without pseudoaneurysm (PSA), and a combination of Glubran 2 and microcoils (n=13) was used for 4 patients (4/10) with PSA. The concentration ratios were 1:2-1:4 mixtures of Glubran 2 and ethiodized oil, and the median total volume injected was 1.1 ml (range, 0.7-1.6 ml). Technical success based on 10 episodes of TAEs was 100% (10/10). Early rebleeding did not occur, and repeat TAE was not necessary. Clinical success was 100% (10/10). No nontarget embolization or embolization-related complications occurred. Two patients (2/10) experienced minor complications of postembolization syndrome. During a median follow-up time of 3 months, no recurrent hemorrhage was recorded. Conclusion Urgent TAE with the use of NBCA Glubran 2 plays an important role in controlling massive PDA hemorrhage. It is minimally invasive, effective, relatively safe, and likely to reduce the need for immediate traditional surgery. The condition with PSA may determine the microcoils employed.